Preparation and photocatalytic activity of carbon coating TiO2 nanotubes. (January 2016) - Kong, Junhan; Wang, Yongqian; Wang, Zhengshu; Jia, Hanxiang
Abstract: Carbon coating TiO2 nanotubes (TNTs) were successfully prepared via anodic oxidation method as well as hydrothermal method, and their photocatalytic activity was evaluated by photodegrading methylene blue. The crystal shape of carbon coating TNTs was affected by the heating treatment temperature and they had a great enhancement on visible light absorption while contrasting with the primitive TNTs. As for photocatalytic activity of carbon coating TNTs in this study, we found that the photo-degradation rate of them can reach to 92.5% after 4 h when the concentration of glucose was 0.025 M. At last, a tentative mechanism for the enhancement of sunlight absorption was proposed. Highlights: The TiO2 nanotubes (TNTs) was prepared via anodic oxidation method. The glucose was used as carbon source in the hydrothermal method for carbon coating. The photocatalytic activity of the carbon coating TNTs we prepared was quite good.